Minimal Requirement for a Lentivirus Vector Based on Human Immunodeficiency Virus Type 1 - Kim, V. Narry (American Society for Microbiology, 1998)
The use of human immunodeficiency virus vectors for gene therapy is hampered by concern over their safety. This concern might be ameliorated, in part, if the viral accessory genes and proteins could be eliminated from the vector genomes and particles. Here we describe a minimal vector system that is capable of transducing nondividing cells and which does not contain tat, vif, vpr, vpu, and nef.